2022
DOI: 10.3389/fnins.2022.1022101
|View full text |Cite
|
Sign up to set email alerts
|

Oro-mucosal administration of oxytocin using medicated lollipops alters social attention, similar to intranasal and lingual routes: Implications for therapeutic use

Abstract: A key functional effect of intranasal administration of the neuropeptide oxytocin is on top-down control of social attention. However, an oro-mucosal administration route may be better tolerated for chronic therapeutic use and evidence suggests that some functional effects of oxytocin can be mediated via peripheral routes. The current study investigated if oxytocin administered orally using medicated lollipops can both increase blood oxytocin concentrations and influence social attention and state anxiety. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 63 publications
(129 reference statements)
0
12
2
Order By: Relevance
“…intravenous, intraperitoneal, subcutaneous and oral). Although, the intranasal administration route for OT produced significantly greater initial increases in plasma OT concentrations compared to an oral route in both the present study, and in two previous ones (Kou et al, 2021;Xu et al, 2022), this did not result in significant route-dependent differences, possibly due to the high doses involved. The broadly similar functional effects of intranasal and oral OT in the context of behavioral and neural responses to gentle stroking touch are also consistent with our previous findings for visual attention towards social and non-social stimuli (Zhuang et al, 2022;Xu et al, 2022), although there is also evidence for route-dependent effects of OT on neural and behavioral effects on responses to emotional faces (Kou et al, 2021).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…intravenous, intraperitoneal, subcutaneous and oral). Although, the intranasal administration route for OT produced significantly greater initial increases in plasma OT concentrations compared to an oral route in both the present study, and in two previous ones (Kou et al, 2021;Xu et al, 2022), this did not result in significant route-dependent differences, possibly due to the high doses involved. The broadly similar functional effects of intranasal and oral OT in the context of behavioral and neural responses to gentle stroking touch are also consistent with our previous findings for visual attention towards social and non-social stimuli (Zhuang et al, 2022;Xu et al, 2022), although there is also evidence for route-dependent effects of OT on neural and behavioral effects on responses to emotional faces (Kou et al, 2021).…”
Section: Discussioncontrasting
confidence: 70%
“…We hypothesized firstly that intranasal OT would particularly enhance behavioral and brain reward (OFC) responses to gentle stroking touch targeting the CT-fiber system in line with previous studies (Chen et al, 2020a; Scheele et al, 2014). Secondly, based on recent studies comparing effects of intranasal and oral OT (Xu et al, 2022; Zhuang et al, 2022), we hypothesized that oral OT would have a similar effect to intranasal OT. Thirdly, we hypothesized that behavioral and neural effects of OT on social touch would be associated with treatment effects on peripheral plasma concentrations of the peptide, in line with observations in some previous studies (Martins et al, 2020; Kou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have used an oral route of administration to demonstrate both neural and behavioral responses to OXT. An oral route precludes any possibility of direct entry into the brain, and using a lingual spray or medicated lollipop, we have shown increased blood concentrations of OXT [24, 25] which we assume are due primarily to absorption via blood vessels in the mouth and tongue since peptidases in the stomach rapidly metabolize OXT without pre-treatment with a gastric acid inhibitor [26]. In an initial study where OXT was administered as a lingual spray to male subjects, increased responses to emotional faces were found in both brain reward (putamen) and emotional-processing (amygdala) regions, with putamen responses to happy faces being associated with increased arousal and mediated by increased plasma OXT concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, intranasal OXT produced reduced amygdala responses to emotional faces and no effect on the putamen at all [24]. Other studies in male subjects have shown that oral OXT administered lingually [27], or using medicated lollipops [25], has an identical effect to intranasal OXT in modulating attention toward social stimuli in an anti-saccade eye-tracking task as well as reduced state anxiety. The effects of oral OXT on attention were also associated with altered plasma OXT concentrations [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation